W ŻALU ZA GRZECHY MŁODOŚCI – TESTAMENT ARMANDA DE BOURBON, KSIĘCIA DE CONTI - Skrzypietz, Aleksandra (Studia Europaea Gnesnensia, 2018)
The paper analyzes the last will of Armand de Bourbon, Prince of Conti, who in his youth abandoned ecclesiastical career and later took active part in the Fronde. Still later, de Bourbon became associated with Jansenists and spent the final years of his life on practicing piety, giving proof of his rigorous morality. The paper thus discusses his last will and professed expiation for the sins of youth, as it attempts to establish whether the testament is a testimony to prince’s Jansenist convictions.